The Influence of Brand Orientation and Knowledge Creation on Organisational Performance of Malaysian Tourist Resorts - Melissa Li Sa Liow,; Kim Chai Yeow,; Choon-Yin Sam,; John Aik Joo Heng, (Asian Academy of Management Journal, 2019)
The purpose of this paper is to examine the effects of brand orientation and knowledge creation process on the organisational performance of tourist resorts from the perspective of tourism entrepreneurs. Despite a plethora of branding and knowledge management literature, a limited number of studies have investigated the effects of brand orientation and knowledge creation process together on organisational performance. The studied tourism entrepreneurs exhibit low involvement in branding activities and knowledge creation according to government of Malaysia sources. The significance of brand orientation and knowledge creation process for improving the organisational performance of tourist resorts remains inconclusive. For this study, empirical data was drawn from 322 tourist resorts in Malaysia. The hypothesised relationships are analysed using structural equation modelling (SEM). The results show that brand orientation and knowledge creation process have a positive and significant effect on organisational performance whereas knowledge creation process partially mediates brand orientation and organisational performance. We propose higher involvement of tourism entrepreneurs in knowledge sharing sessions to develop distinctive brands to attract customers, which will in turn improve organisational performance. The top-down management approach in instituting branding activities remains pervasive in tourist resorts in Malaysia’s high-power distance society.